DIGITALIZATION DOCUMENT CONTROL AND DATA RECORDS MANAGEMENT TO SUPPORT BUSINESS INTELLIGENCE OF INTEGRATED DOCUMENTED INFORMATION CONTROL ACTIVITIES AT PT X - Sertiya Putri, Kartika Dyah; Yulianti, Praptini (Transpublika Publisher, 2024)
Digitalization plays an important role in improving document control and data records management to support documented information control activities that integrate business intelligence. This research aims to analyze the impact of digitization in document control and data records management at PT X, as well as how digital technology can improve the efficiency and effectiveness of documented information management. This research uses a descriptive method with a qualitative approach, in the form of a case study at PT X. Primary data was obtained through in-depth interviews with PT X system management staff and direct observation, while secondary data was collected from company documents, annual reports, applied ISO standards, and related literature. The data analysis technique used was thematic analysis. The results showed that a digital document management system can organize documents more efficiently, enable easier and faster access, and improve compliance with ISO standards. Digitalization in document control and records management at PT X resulted in improved operational efficiency, regulatory compliance, and competitive advantage. This research emphasizes the importance of managerial support and organizational culture change in the implementation of digital technology. Thus, the integration of digital solutions not only facilitates better information management but also supports the continuous improvement and business success of PT X in the modern business landscape.